Advanced Remote Training on ENACTS Tools for the Kenya Meteorological Department (KMD) - Faniriantsoa, Rija; Dinh, Dannie (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report summarizes a series of technical trainings conducted by the International Research Institute for Climate and Society for Kenya Meteorological Department (KMD) staff. The series is part of IRI's continued efforts to strengthen the technical capacity of KMD staff, enabling them to stay current with recent evolution of the Enhancing National Climate Services (ENACTS) tools and products.